FILSAFAH KEHIDUPAN TRITANGTU SUNDA DALAM FILM EKSPERIMENTAL ADAT “GAME OVER DRAMA” - Wiki Riandi; Erik Muhammad Pauhrizi; Sandie Gunara (Jurnal Adat dan Budaya Indonesia, 2023)
Creating an art work is a creative process of thinking and emotion in a practical and intuitive performance. Personal coding of the author in the creation of experimental film often leads to new interpretations. The empirical experience of tradition underlies the idea of creating a notable work. Sundanese Tritangtu philosophy, a tradition of the Sundanese, contributes to the formation of sundanese's creativity in working and understanding life. In this study, an experimental film entitled "Game over Drama" was interpreted heurmeneuticly with the concept of Tritangtu with the aim of making a systematic, factual visual description, and raising awareness of the Sundanese about the relationship between humans, nature and their gods. The analysis focused on the film visual content to reveal the Sundanese Tritangtu philosophy. The results of this study reveal that the Sundanese always consider that their lives will always depend on nature and their Creator and believe that their bodies are composed of elements of water, earth, air and fire which are natural elements. This view is a relationship manifestation between the Sundanese and the universe as well as a representation of the characters contained in their bodies. This research is expected to be a reference for exploring the values of local wisdom for filmmakers who try to raise local wisdom through experimental films.